Penggunaan Etika Bahasa Yang Tepat Dan Etis Di Media Sosial (Instagram) - Fathin Azzam Abdulhaq,; Fauzan ghilar ibrahim, (Student Scientific Creativity Journal, 2023)
Social media is online media, by the way, its users can easily participate, share and create content easily. The development of social media is very rapid lately. So it becomes a hot topic that deserves discussion because many people use social media without realizing the meaning of the media itself. The social media used is Instagram. Instagram is a powerful social networking media application that generates and publishes photos instantly. The development of social media directly affects the order of human behavior, both as a means of information and as a means of socialization and interaction between people. Social media seems like the go-to place for all inactivity Rarely goes beyond existing codes of conduct. In terms of the use of language that is not standard and informal in communication. Communication is the process of adding information (messages, ideas, thoughts) from one party to another. Communication will be more effective if the message conveyed can be received, the message is interpreted the same. Good Communication Ethics Social media may not use harsh, provocative, pornographic or Sara.